Research on Incentive Mechanism and Evaluation of Gamification Application for Sustainable Consumption in the Context of China - Sun, Shouheng; Wang, Zhenqin; Wu, Qi; Wang, Weicai (Frontiers in Sustainability, 2022)
The gamification of sustainable consumption is receiving more and more attention from both academic and business circles. However, there is still a lack of research on the incentive mechanism and evaluation of gamification design to promote sustainable consumption behavior. Taking the gamified apps that promote sustainable consumption in China as an example, this study attempts to explore the incentive mechanism of gamification application for sustainable consumption by using the “stimulus-organism-response” model. Furthermore, it also constructs an evaluation index system of gamification design for sustainable consumption app and identifies the key factors in the gamification design by using the analytic hierarchy process. The results suggest that gamification apps use game elements and game mechanism frameworks to build a new sustainable consumption context for users, which breaks the boundary between reality and virtuality, and enables users to gain real-life value for their behavior in the virtual world. Moreover, the trust mechanism and socialized contextual experience of the gamified apps further strengthen this sense of connectedness and interaction, and enhance the user's motivation for sustainable consumption. In the gamification design of sustainable consumption app, more attention needs to be paid to the implementation effect behind gamification, that is, to promote the cultivation of public sustainable consumption values and lifestyle. This study advances theoretical and practical understanding of the gamification of sustainable consumption. The results can also be used as a starting base for the development and design of gamified apps in the sustainable consumption field.